Perfil clínico funcional de pacientes con artritis reumatoide derivados a Fisiatría en control en Centro Reumatólogico Avanzado (CREA) del Hospital Clínico Universidad de Chile - Rivera R., Carolina; Vergara B., Loreto; Prieto S., Stephanie; Castro L., Ariel (Revista Hospital Clínico Universidad de Chile, 2018)
Background: Rheumatoid arthritis (RA) is a systemic inflammatory disease that primarily affects the joints causing varying degrees of disability. Non-pharmacological management is increasing evidence of its usefulness impacting functionality. Objectives: To characterize the clinical / functional profile of patients with rheumatoid arthritis derived physiatrist assessment in the Clinical Hospital University of Chile. Methods: We reviewed the clinical records of patients with RA derivatives Physical Medicine, extraction demographics, medical history, physical examination and functionality. Statisticians analysis of central tendency, dispersion, absolute and relative frequencies. Results: 85 medical records were analyzed. 88.2% were women with an average age of 54.05 ± 11.42 years. 38.8% have at least one comorbidity. 34.1% of patients takes between 6 and 15 years of disease. The average drug related AR is 5.6 per patient, being more Disease Modifying Antirheumatic Drugs (DMARDs) found. 35.2% presented falls in the past year. Pain is a symptom found in the history and physical examination with a VAE (venous air embolism) 4.4 ± 2.43 at the time of consultation and 6.7 ± 3.3 in crisis. 20% received kinesic therapy and only 7% occupational therapy. 45.3% of patients having a value of HAQ (health assesment questionnaire) who scored as moderate disability, even if their self-perception of independence reaches 65.9%. Conclusion: The analysis allows us to perform a demographic, clinical and functional profile that allows us to guide rehabilitation actions.